2018
DOI: 10.21315/jps2018.29.s3.9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of PO43- Removal from Aqueous Solution with Varied Concentrations of Metal Oxides in Steel Slag Filter System

Abstract: High amount of orthophosphate will accelerate the growth of autotrophs and eutrophication will occur. This phenomenon decreases the water quality and as a result may increase the cost of water treatment for drinking water. The overabundance of orthophosphate occurs when untreated or inadequately-treated wastewater from domestic and industrial activities is released into water bodies. Conventional treatment has been developed to treat wastewater. However, it is not effective for phosphorus removal, hence, high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
1
2
2
Order By: Relevance
“…According to Barca et al [29], precipitation mechanism occurs when the liberated Ca 2+ from the exchange site or from the dissolution of CaCO3, CaO and Ca(OH)2 were precipitated by phosphate in a neutral to alkaline solution producing white precipitated in the filter. Furthermore, findings from Hamdan et al [30] also similar to Barca et al [29] when using synthetic wastewater as feed [16]. This result was also similar with both studies where the precipitation was dominant at alkaline pH for USSF due to the formation precipitated at the bottom of the filter.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…According to Barca et al [29], precipitation mechanism occurs when the liberated Ca 2+ from the exchange site or from the dissolution of CaCO3, CaO and Ca(OH)2 were precipitated by phosphate in a neutral to alkaline solution producing white precipitated in the filter. Furthermore, findings from Hamdan et al [30] also similar to Barca et al [29] when using synthetic wastewater as feed [16]. This result was also similar with both studies where the precipitation was dominant at alkaline pH for USSF due to the formation precipitated at the bottom of the filter.…”
Section: Resultssupporting
confidence: 81%
“…This result was also similar with both studies where the precipitation was dominant at alkaline pH for USSF due to the formation precipitated at the bottom of the filter. However, the precipitates were brown which contradicting with Hamdan et al [30] and Barca et al [29] since both of the research have white crystalline precipitate. The brown precipitate were probably due to the reaction between Feric oxide present in the slag which indicates the reaction between the liberated Fe 2+ or the dissolution of Fe2O2 and Fe(OH)2 from the steel slag and phosphorus in the wastewater [30].…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…However, the precipitates were brown, which contradict with Hamdan et al and Barca et al, since both of the research reported white crystalline precipitate. The brown precipitate was probably due to the reaction between ferric oxide present in the slag, which indicates the reaction between the liberated Fe 2+ or the dissolution of Fe2O2 and Fe(OH)2 from the steel slag and phosphorus in the wastewater [9]. On the other hand, brown layer of adsorbate was also found on the surface of the slag formed in ASSF, most likely due to the binding of Fe 2+ present in the steel slag surfaces with PO4 3in the wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…However, the permissible discharged limit was quite high, as Alamdari et al [8] stated that even a slight rise of 0.1 Mg/L of P can promote growth of algae in the water body, which is also known as eutrophication. The excessive growth of algae utilises all the oxygen concentration in the water body, making it unsuitable for aquatic life [9]. Degradation of water quality was unavoidable thus adding water quality crisis to the list of problems.…”
Section: Phosphorus In Textile Wastewatermentioning
confidence: 99%